The Role of Quality of Work Life on Performance Appraisal - Samrin (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The purpose of this study is to determine the effect of quality of work life factors consisting of career development, communication and compensation partially and simultaneously have a positive and significant impact on employee performance. The method of analysis used is quantitative analysis method. Types of data used are primary data obtained through interviews and questionnaires whose measurement using a Likert scale and processed statistically using SPSS 16.0 for window program that is F-test model, t-test, and determination (R²). The results obtained from this study indicate that simultaneously the quality of work life factors consisting of career development, communication and compensation have the positive and significant effect on employee performance. Partially can be seen that the factors of quality of work life which consists of career development, communication and compensation have a positive and significant impact on employee performance. Test R2 can be seen number adjusted R Square or determinant (R2) equal to 0.886. This figure means that the effect of career development, communication, and compensation on employee performance is 88.6 percent. The remaining 11.4 percent influenced by other factors not included in the variables not included in this study.